2022
DOI: 10.21203/rs.3.rs-1930069/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NH3 emissions over Europe during COVID-19 were modulated by changes in atmospheric chemistry.

Abstract: The coronavirus outbreak in 2020 had devastating impact on human life, albeit a positive effect for the environment reducing primary atmospheric constituents and improving air quality. Here we present for the first-time inverse modelling estimates of ammonia emissions during the European lockdowns based on satellite observations. Ammonia that originates mainly from agriculture is not projected to be strongly influenced by restrictions, as practically agricultural activity never ceased. The key result is a -1.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…For April 2020, the Chinese emission inventory (29) reported that the primary aerosol emission reductions relative to April 2019 recovered to 10%. Globally, NH 3 emission reductions remain uncertain, while European NH 3 emissions were estimated to be reduced by 13% during the COVID-19 lockdown according to the CrIS satellite measurement (59). To confirm the potential impacts of these reductions, additional CTM simulations by changing primary aerosols' and NH 3 emissions (CTM_SN2020+PA and CTM_SN2020+A-, respectively) were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…For April 2020, the Chinese emission inventory (29) reported that the primary aerosol emission reductions relative to April 2019 recovered to 10%. Globally, NH 3 emission reductions remain uncertain, while European NH 3 emissions were estimated to be reduced by 13% during the COVID-19 lockdown according to the CrIS satellite measurement (59). To confirm the potential impacts of these reductions, additional CTM simulations by changing primary aerosols' and NH 3 emissions (CTM_SN2020+PA and CTM_SN2020+A-, respectively) were conducted.…”
Section: Discussionmentioning
confidence: 99%